Globalización y cultura Dimensiones peruanas * - Mejia Navarrete, Julio (2007)
Along the last few years in Peru, and more generally in Latin America, a vast social movement is taking place. It is a very diverse, sometimes even contradictory, movement that appreciates local identities with clear elements from the Andean universe, in the midst of a globalisation dynamics that seemed imminent and absolute. We gradually assist to a process whereby peoples reinforce a sense of national unity and reclaim their rights to exist beyond the global standardisation pattern. Our paper is far from finished but is a starting point to develop some key aspects of the relationship between globalisation and culture in Peru, that have not yet been adequately studied.